Protein lysine methylation contributes to modulating the response of sensitive and tolerant Arabidopsis species to cadmium stress. (8th December 2019) - Serre, Nelson B. C.; Sarthou, Manon; Gigarel, Océane; Figuet, Sylvie; Corso, Massimiliano; Choulet, Justine; Rofidal, Valérie; Alban, Claude; Santoni, Véronique; Bourguignon, Jacques; Verbruggen, Nathalie; Ravanel, Stéphane
Abstract: The mechanisms underlying the response and adaptation of plants to excess of trace elements are not fully described. Here, we analysed the importance of protein lysine methylation for plants to cope with cadmium. We analysed the effect of cadmium on lysine‐methylated proteins and protein lysine methyltransferases (KMTs) in two cadmium‐sensitive species, Arabidopsis thaliana and A . lyrata, and in three populations of A . halleri with contrasting cadmium accumulation and tolerance traits. We showed that some proteins are differentially methylated at lysine residues in response to Cd and that a few genes coding KMTs are regulated by cadmium. Also, we showed that 9 out of 23 A. thaliana mutants disrupted in KMT genes have a tolerance to cadmium that is significantly different from that of wild‐type seedlings. We further characterized two of these mutants, one was knocked out in the calmodulin lysine methyltransferase gene and displayed increased tolerance to cadmium, and the other was interrupted in a KMT gene of unknown function and showed a decreased capacity to cope with cadmium. Together, our results showed that lysine methylation of non‐histone proteins is impacted by cadmium and that several methylation events are important for modulating the response of Arabidopsis plants to cadmium stress. Abstract : The mechanisms underlying the response and adaptation of plants to excess of trace elements are not fully described. Here, we showed that lysine methylation of non‐histone proteins is part of the regulatory mechanisms helping plants to cope with the toxic metal cadmium.